Varicella Zoster Virus-Specific Hyperimmunoglobulin in the Adjuvant Treatment of Immunocompromised Herpes Zoster Patients: A Case Series - Terheyden, Patrick; Sunderkötter, Cord; Söhngen, Franz Dietmar; Golle, Linda; Schimo, Sonja; Baron, Ralf; Maihöfner, Christian; Binder, Andreas; Pönisch, Wolfram (Dermatology and Therapy, 2023)
Introduction: Immunocompromised patients are at increased risk for herpes zoster (HZ)-associated complications. Despite standard therapy with systemic antiviral drugs and analgesics, complications are frequently encountered, including generalization of lesions or persistent neuropathic pain, so-called post-herpetic neuralgia (PHN). Given the scarcity of literature and awareness of therapeutic options to improve patient outcomes, especially for vulnerable patient groups, here we describe a strategy based on early intensification of treatment with a varicella zoster virus-specific hyperimmunoglobulin (VZV-IgG), which is approved in the adjuvant treatment of HZ. Methods: For this case series, we selected four cases of HZ in patients with impaired immunity due to hemato-oncologic disease or immunosuppressive treatment who presented with either existing generalized lesions and/or severe pain or with other risk factors for a complicated HZ course such as PHN. They were considered to be representative examples of different patient profiles eligible for intensification of treatment by the addition of VZV-IgG to virostatic therapy. Case Report: All patients showed a rapid response to combined treatment with VZV-IgG and a virostatic agent. In two patients who had generalized lesions, the formation of new lesions ceased 1 day after VZV-IgG infusion. One patient, with mantle cell lymphoma, achieved complete healing of the lesions 9 days after diagnosis of HZ, a rare occurrence compared to similar cases or cohorts. A patient with HZ in the cervical region showed a good response after a single dose of VZV-IgG. None of the patients developed post-zoster-related complications. Combination therapy of a virostatic agent and VZV-IgG was well tolerated in these four cases. Conclusion: This case series demonstrates highly satisfactory treatment effectiveness and tolerability for VZV-IgG in the adjuvant treatment of immunocompromised HZ patients and supports early intensification of HZ therapy in patients at high risk of severe disease progression.
CRIS-Team Scopus Importer:2023-09-22
Keywords: Generalized lesions; Herpes zoster; Hyperimmunoglobulin; Immunocompromised; Varitect CP; VZV; VZV-IgG